2017
DOI: 10.1007/s10120-017-0691-z
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of extragastric recurrence and the role of abdominal computed tomography in surveillance after endoscopic resection of early gastric cancer: Korean experiences

Abstract: Background Although extragastric recurrence after endoscopic resection of early gastric cancer is rare, it is important because of its potentially fatal outcomes. We investigated the patterns of extragastric recurrence after endoscopic resection and evaluated the role of abdominal computed tomography in surveillance. Methods Between July 1994 and June 2014, 4915 patients underwent endoscopic resection of early gastric cancer. Because of follow-up periods of less than 6 months and consecutive surgery within 1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…101 In another Korean study on 15 cases of extra-gastric recurrence published in 2017, 66.7% (4/6) of expanded criteria lesions and 83.3% (5/6) of out-of-indication lesions showed extra-gastric recurrences on CT without any intragastric recurrences, demonstrating the need for follow-up CT in patients with expanded criteria lesions. 194 However, another Korean study reported detecting extra-gastric lymph node recurrence on CT in only two (one case of absolute criteria and one of expanded criteria) among total of 2,182 patients who underwent curative endoscopic resection, suggesting that CT after curative endoscopic resection is unnecessary for patients who meet expanded criteria considering the cost and radiation dose of CT. 195 In addition, a study that followed up 894 mucosal cancers using endoscopy and abdominopelvic CT following their curative endoscopic resection reported CT signs of recurrence in only two cases, suggesting that CT plays a minimal role in follow-up after endoscopic resection. 196 Precise standards for the target subjects and interval of follow-up abdominopelvic CT are yet to be established, and further research is needed in this regard.…”
Section: Statement G13mentioning
confidence: 99%
“…101 In another Korean study on 15 cases of extra-gastric recurrence published in 2017, 66.7% (4/6) of expanded criteria lesions and 83.3% (5/6) of out-of-indication lesions showed extra-gastric recurrences on CT without any intragastric recurrences, demonstrating the need for follow-up CT in patients with expanded criteria lesions. 194 However, another Korean study reported detecting extra-gastric lymph node recurrence on CT in only two (one case of absolute criteria and one of expanded criteria) among total of 2,182 patients who underwent curative endoscopic resection, suggesting that CT after curative endoscopic resection is unnecessary for patients who meet expanded criteria considering the cost and radiation dose of CT. 195 In addition, a study that followed up 894 mucosal cancers using endoscopy and abdominopelvic CT following their curative endoscopic resection reported CT signs of recurrence in only two cases, suggesting that CT plays a minimal role in follow-up after endoscopic resection. 196 Precise standards for the target subjects and interval of follow-up abdominopelvic CT are yet to be established, and further research is needed in this regard.…”
Section: Statement G13mentioning
confidence: 99%
“…In Korea, the annual incidence of AGS is estimated to be 29,207; this represents > 4% of the global annual incidence [1113]. Moreover, gastric cancer patients in Asian countries have a significantly higher 5-year survival rate than those in Western countries [14].…”
Section: Introductionmentioning
confidence: 99%
“…50 A Korean large-scale single center study also showed that 0.14% (5/3,588) of patients with curative resection and expanded curative resection underwent recurrence after ESD. 51 Another study from Korea reported 0.15% (2/1,306) of recurrence after curative resection and expanded curative resection. 52 In these studies, most patients with curative resection and expanded curative resection have favorable long-term outcomes after ESD for EGC; however, it should be noted that a very small number of patients with expanded curative resection have recurrence.…”
Section: Long-term Outcome and Recurrencementioning
confidence: 99%